Design of an Autonomous and Timed Water Delivery System in Microgravity - Elke, William; Heineck, Maia; Meffert, Jonah; Monaghan, Ellie; Palesse, Jason (Proceedings of the Wisconsin Space Conference, 2020)
For long-duration, manned, space exploration missions to be feasible, farming techniques in space must become reliable and fruitful. The NASA Project Veggie team currently runs experiments on the International Space Station (ISS) in order to better understand how plants react to a microgravity environment. Current watering strategies on the ISS involve manual watering of all plants by the crewmembers. This poses a problem because watering plants must be scheduled into the crewmembers’ days which means less time to work, etc. The objective of Team International Space Salads (ISSa) was to create a device and prove that it could function in microgravity without electricity to autonomously water the plants in order to allow for schedule flexibility of the ISS crewmembers and to lay the foundation for watering systems for deep-space travel. The final device did not function fully as planned, however, the plant growing, surface tension experiments, and the device collectively progressed the multi-year project to a state where successive teams would have the knowledge and tools necessary to create a fully functioning device.